TANGGUNG JAWAB BANK DALAM PENERBITAN ATM (AUTOMATIC TELLER MACHINE) DAN PERMASALAHAN YANG TIMBUL SERTA PENYELESAIANNYA - Khamami Noval Abidin (Journal of Law ( Jurnal Ilmu Hukum ), 2019)
ABSTRACTKhamami Noval Abidin, NPM: 13.11.1001.1011.046, "Responsibility Bank In Publishing ATM (Automatic Teller Machine) And Problems That Occur And Solved". (Guided by Isnawati, SH., MH and Drawan Hasyim, S.H ,. M.Si).This study was conducted to determine the responsibility of the Bank in the issuance of ATM and problems that arise and how the completion of the issuance of ATM. In collecting the data, the writer used the normative from various sources of literature of library materials by examining the materials in the library. And the data were analyzed using analysis description, which gives a very clear picture about the responsibility of the Bank in the issuance of ATM and problems that arise and how the completion of the issuance of ATM.The results showed that with the issuance of ATM can provide transaction facilities are equipped with all the advantages that exist and the different costs per ATM card ownership. To have an ATM card, the customer must first be asked to fill out a form and meet the terms and conditions set by the Bank, and agreements that have been agreed which binds itself to Bank customers and give approval. Problems arising from the issuance of ATM is limited between the customer and the Bank without the need to go to court, and the Bank will be responsible for the use of existing facilities at the ATM card, if there is a case in connection with the possession of an ATM card with the exception of the error caused by the customer's own. Keywords  : Bank, ATM (Automatic Teller Machine)